2014
DOI: 10.1001/jama.2014.9743
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management ofStaphylococcus aureusBacteremia

Abstract: Importance Several management strategies may improve outcomes in patients with Staphylococcus aureus bacteremia (SAB). The strength of evidence supporting these management strategies, however, varies widely. Objective To perform a systematic review of the evidence for two unresolved questions involving management strategies for SAB: 1) is transesophageal echocardiography (TEE) necessary in all cases of SAB; and 2) what is the optimal antibiotic therapy for methicillin resistant Staphylococcus aureus (MRSA) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
261
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(282 citation statements)
references
References 99 publications
3
261
1
2
Order By: Relevance
“…6 However, their effectiveness is declining. 5 Much evidence has shown that the increased resistance of vancomycin has led to poor therapeutic outcomes and increased patient mortality.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, their effectiveness is declining. 5 Much evidence has shown that the increased resistance of vancomycin has led to poor therapeutic outcomes and increased patient mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with S. aureus bacteraemia should undergo echocardiography because of the high frequency of IE in this setting. TTE may be adequate in a carefully selected minority of patients who do not have a permanent intracardiac device, have sterile follow-up blood cultures within 4 days after the initial set, are not haemodialysis dependent, have nosocomial acquisition of bacteraemia, do not have secondary foci of infection and do not have clinical signs of IE 105 . To differentiate patients with S. aureus bacteraemia who are at high risk of IE from those at low risk, several scoring systems have been proposed [106][107][108][109][110] although none has been prospectively evaluated.…”
Section: Diagnosis Screening and Prevention Diagnosismentioning
confidence: 99%
“…Antistaphylococcal β-lactam antibiotics are recommended whenever possible for MSSA-associated IE, as data from observational studies suggest worse outcomes for patients with MSSA bloodstream infections who are treated with vancomycin 105,139 . Whether it is necessary to use a β-lactam antibiotic as empiric therapy is unclear; small retrospective studies have suggested a potential benefit 140 .…”
Section: Organism-specific Considerationsmentioning
confidence: 99%
“…In 2014, in the UK alone, there were 9,100 cases of SAB reported in Public Health England's voluntary surveillance database, [4] care, and administering appropriate antibiotics for a sufficient length of time [1][2][3]5,6].…”
Section: Introductionmentioning
confidence: 99%